Teacher Competence in Independent Learning Evaluation - Tumiran, Tumiran; Azhar, Abdul Izul; Sirait, Syarifuddin; Saragih, Siti Sahrapmahita; Nasution, Napsiah (Journal of English Language and Education, 2025)
The purpose of this study is to analyze Teacher Competence in the Evaluation of Independent Learning. The method used in this study is the library research method ( Library Research ), with a qualitative approach. Library research is a study that uses a method of obtaining all information data to locate existing facilities in the library, such as books, magazines, documents, and records of historical stories. From the problems discussed, the researcher uses a philosophical approach. So that the object of the study is Teacher Competence in the Evaluation of Independent Learning. In data collection techniques, the researcher uses documentation materials. The researcher himself is the core instrument. The researcher uses content analysis . Content analysis is used to analyze all forms of communication such as documentation materials and others. And the data can be obtained, which then the researcher processes the data by reading, recording and analyzing by concluding. The results of this study indicate that this evaluation activity is important to review the success of learning in the era of learning independence. Therefore, teachers must have the ability to carry out evaluations. The objectives of this study include 1) Understanding the concept of learning evaluation 2) explaining teacher competencies in carrying out learning evaluations. The method used in writing this journal is a literature study in which research data obtained from several library theories are processed and analyzed and then described, so that it is obtained. The results of the study indicate that teachers need to understand the concept of evaluation as a whole, including the definition, purpose, function, principles, and types of learning evaluation. Teacher competencies in evaluation include the ability to design, implement, process data, report, and utilize evaluation results to improve learning in the future